NECESSITY TO VALORIZE TRAINING EFFECTS IN RECREATION - Budimir Bijelić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
A real need for up-to-date and uniform evaluation of fitness abilities of different social and age categories of our town inhabitants has existed for many years in different circles of population and population in the whole. The research results presented in this paper mean just an attempt to »open the problem « and explain only some of data obtained with quite uniform groups who took part in the sports-recreation projects. According to the results obtained we can assume that our local male population, age 40 and over, have a tendency of "worryingly" high drop of aerobic, working and overall fitness abilities